Sirolimus as Rescue Therapy for Refractory/Relapsed Immune Thrombocytopenia: Results of a Single-Center, Prospective, Single-Arm Study - Feng, Yimei; Xiao, Yunshuo; Yan, Hongju; Wang, Ping; Zhu, Wen; Cassady, Kaniel; Zou, Zhongmin; Wang, Kaifa; Chen, Ting; Quan, Yao; Wang, Zheng; Yang, Shijie; et al. (Frontiers in Medicine, 2020)
Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease which arises due to self-destruction of circulating platelets. Failure to respond or maintain a response to first-line treatment can lead to refractory/relapsed (R/R) ITP. The mechanism remains complicated and lacks a standard clinical treatment. Sirolimus (SRL) is a mammalian target of rapamycin (mTOR) inhibitor that has been demonstrated to inhibit lymphocyte activity, indicating potential for SRL in treatment of ITP. Activation of the mTOR pathway in autoimmune diseases suggests that SRL might be a useful agent for treating ITP. Accordingly, we initiated an open-label, prospective clinical trial using SRL for patients with R/R ITP (ChiCTR-ONC-17012126). The trial enrolled 86 patients, each dosed with 2-4 mg/day of SRL. By the third month, 40% of patients (34 of 86) achieved complete remission (CR) and 45% of patients (39 of 86) achieved partial remission (PR), whereby establishing an overall response rate (ORR) of 85%. By 6-months of treatment, 41% of patients (32 of 78) achieved CR and 29% of patients (23 of 78) achieved PR, establishing an ORR of 70% without serious side effects. After 12-months follow-up, the ORR remained at 65%. We also found that SRL treatment exhibited higher efficacy in achieving CR in ITP patients who were younger than 40 years old or steroid dependent. Importantly, in patients who responded, SRL treatment was associated with a reduction in the percentage of Th2, Th17 cells, and increase in the percentage of M-MDSCs and Tregs, indicating that SRL may reestablish peripheral tolerance. Taken together, Sirolimus demonstrated efficacy as a second-line agent for R/R ITP.